The condition requirements for optical bistability in semiconductor laser under injection locking - A. I. Abdullah; M. S. Mohammed (College of Education for Pure Sciences, 2008)
Abstract The experimental fulfillment for optical bistability in a semiconductor laser under injection locking is studied. The required setup to provide the stability in current, temperature and power output of the laser diode used in experiments has been described in detail. A small change in the injection power of the slave laser SL could induce a dynamic change of the lasing power of the master laser ML has been observed. Optical bistability for two non identical laser was possible has been experimentally observed.